Degradation of textile dyes in aqueous solutions using type-Fenton bimetallic zeolite catalysts - Santos, Bebiana L. C. (2019)
[Excerpt] Textile dyes are growing to be a problematic class of pollutants to the environment. The disposal of dyes in water resources has bad aesthetic and health effects, since most of them are carcinogenic and mutagenic [1,2], so it is important to remove them from the environment. Effective and economic treatment by advanced oxidation processes (AOPs) has been attracted great and continuous interest for the degradation of these pollutants [3]. [...]